Moving milk and shifting risk: A mixed methods assessment of food safety risks along informal dairy value chains in Kisumu, Kenya - Smith, L.C.; Stringer, A.; Owuor, K.O.; Ndenga, B.A.; Winter, C.; Gerken, Keli N. (Elsevier, 2024)
Animal sourced foods (ASF) are important for global food security and in mitigating the impact of undernutrition. Across Sub-Saharan Africa, demand and urbanization continue to increase, creating a greater divide between farm-level production and consumption. Food safety residues including antibiotics and aflatoxin residues often originate at the production site, and risk can shift as milk is transported. In 2022, milk samples (n = 190) were collected from eight milk vendors in Kisumu, Kenya and tested for betalactams and aflatoxins with cut off values of 300 parts per billion (ppb) and 200 parts per trillion (ppt), respectively. Data was collected on the origin and containers of each sample, and the eight vendors responded to an open-ended questionnaire regarding the structure and challenges in their milk business. Aflatoxin residues were detected in 7 % (13/190) of samples with no samples (0/190) testing positive for antibiotic residues. Overall, 80 % samples were collected from metal transportation containers, and no milk containers >20 l tested positive for aflatoxins. The origin location(s) of milk was not significantly associated with residues (p = 0.44). Vendor questionnaire data were summarized into three themes: 1) Physical properties of milk are understood to influence quality, 2) Fluctuating availability of milk impacts profits and is the main influence on choice of supplier, and 3) Trust and rapport among value chain actors are key to mitigating business challenges. Our results indicate that farm-level practices around antibiotic use is not posing a major milk safety risk to urban consumers. Use of large 50-l containers for transporting milk may be protective as risk of aflatoxin residues is diluted below key thresholds. We recommend supporting existing relationships and identifying drivers that build trust among informal value chain actors which could strengthen collaboration and allow actors to move towards a shared goal of reliable and safe milk available for urban consumers.